Augmentation Mastopexy with Implant and Autologous Tissue for Correction of Moderate/Severe Ptosis. (2nd January 2016) - Ferraro, Giuseppe Andrea; De Francesco, Francesco; Razzano, Sergio; D'Andrea, Francesco; Nicoletti, Gianfranco
ABSTRACT: Purpose: Breast augmentation combined with mastopexy is associated with a significantly higher complication rate than augmentation alone. The combination of mastopexy and breast implants has revealed a moderate recurrence of breast ptosis in many patients particularly with use of medium to large implants. Ptosis is the "bottoming out" of the breast tissue with loss of the desired roundness, due to the ptosis of the breast implant and the mammary tissue. In this study, we hypothesize the need for careful planning and careful preoperative surgical execution to minimize this complication. Patients and Methods: Between January 2007 and July 2011, augmentation mastopexy with implant and autologous tissue ("double implant") was performed for 25 patients with grade III mammary ptosis. All patients underwent inverted-T mastopexy with supramuscular moderately cohesive gel breast implant using an inferior-based flap of de-epitelialized dermoglandular tissue and a superior-based nipple-areola complex pedicle. Results: An inferior-based flap of deepithelialized dermoglandular tissue was used to stabilize the implant and is projection. Breast lifting was performed through a strong anchorage to fascia and to muscle of second intercostal space, improving the profile of the breast. Results were analyzed, no breast ptosis recurrence was noted at 30-month follow-up. Conclusions: Our technique presents the challenge of determining the amount of excess skin to be removed after implantation to create symmetry and provide for skin tightening without compromising tissue vascularization.